EKSPLORASI FAKTOR YANG MEMPENGARUHI TINGGINYA PERSEDIAAN SEMEN PADA PT BERHASIL INDONESIA GEMILANG - Ardhika Wisnu Wardana; Bambang Tjahjadi (Politeknik Negeri Lhokseumawe, 2021)
PT. Berhasil Indonesia Gemilang officially operated since 19 November 2014, BIG is a company engaged in the distribution services of cement products. Good inventory management is expected to replenish each other and can strengthen the position in the distribution to customers and given the best service. An average about 470,700 Bag, in the year 2016 , in the year 2017 the average of the plot 1,172,584 Bag and in the year 2018 the average supply of 1,778,121 Bag from the data recorded from the year 2016-2018 there is a drastic increase in inventory supplies. Data analysis uses cause and effect diagrams or fish bone diagrams to determine the underlying cause of increased inventory supplies. The result of the analysis will know the cause of inventory supplies.Keywords: Stock, cement, fish bone diagram